Nas águas do velho Chico : por uma arqueologia de ambiente aquáticos no baixo Rio São Francisco - Sergipe/Alagoas - Freire, Luís Felipe (2013)
The recent research aims at an idealization of an Archaeology of Aquatic Environment worried in inserting multiple voices in the process of the construction of the knowledge, making it possible to bring closer society to archaeological research and to its heritage. Through the presentation and the discussion of a theoretical-methodological framework of an integrative and multivocal bias and through the contextualization of the researched area, the lower São Francisco River, it’s sought to draw a line in a position in which Archaeology is capable to comprehend the many relationships existent between local communities and its archaeological heritage. Thus, the sub aquatic archaeology research rises as a form to mediate a relation of self-recognition of society to its underwater cultural heritage.